1992
DOI: 10.1152/ajpcell.1992.262.4.c941
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple mechanisms including phospholipase D by endothelin-1 in rat aorta

Abstract: This study investigated the cellular mechanisms underlying the endothelin-1 (ET-1)-induced contraction of rat aorta with focus on the involvement of phospholipase D (PLD). Preincubating rat aorta in Ca(2+)-free solution reduced the contraction by 80%, whereas diltiazem (10 microM), a voltage-operated Ca2+ channel blocker, caused only a small reduction (27%, P less than 0.05) of the contraction. In myo-[3H]inositol-labeled aorta, ET-1 stimulated the formation of [3H]inositol bisphosphate and [3H]inositol trisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…9,17 ET-1 is a 21-aminoacid peptide that binds to ETA-type receptors expressed on smooth muscle cells inducing a vasoconstrictor response. 18,19 Interestingly, ET-1 is also capable of stimulating the production of superoxide anion by several types of cells. 20,21 In our study, a specific antagonist of the ETA-type receptors, BQ-123, normalized the endotheliumdependent vasorelaxing response impaired by sevoflurane suggesting that vasoconstriction related to ET-1 could be counterbalancing the NO-dependent vasorelaxing system in sevoflurane-incubated aortic segments.…”
Section: Involvement Of Et-1 In the Endothelial Dysfunction Induced Bmentioning
confidence: 99%
“…9,17 ET-1 is a 21-aminoacid peptide that binds to ETA-type receptors expressed on smooth muscle cells inducing a vasoconstrictor response. 18,19 Interestingly, ET-1 is also capable of stimulating the production of superoxide anion by several types of cells. 20,21 In our study, a specific antagonist of the ETA-type receptors, BQ-123, normalized the endotheliumdependent vasorelaxing response impaired by sevoflurane suggesting that vasoconstriction related to ET-1 could be counterbalancing the NO-dependent vasorelaxing system in sevoflurane-incubated aortic segments.…”
Section: Involvement Of Et-1 In the Endothelial Dysfunction Induced Bmentioning
confidence: 99%
“…This mitogenic activity has been associated with the stimulated expression of the protooncogenes c-fis and c-myc in both smooth muscle cells [2] and fibroblasts [4]. ET-l acting at ET, receptors is known to stimulate both phospholipase C (PLC) [3,4] and phospholipase D (PLD) [5] in vascular smooth muscle cells. Phosphatidic acid is the primary lipid product of PLD, and it (or its lyso derivative) may be mitogenic in its own right [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase D, which is known to be activated by endothelin-1 and which will generate diacylglycerol and thus activate protein kinase C independently of phospholipase C, could play a role in modulating platelet pH without significantly altering cytosolic calcium. 43 Intracellular alkalinization induced by Ang II and endothelin-1 are probably related to stimulation of the Na + -H + exchanger. We have shown that in the presence of a highly specific Na + -H + exchange blocker, the normal alkalinization responses to Ang II and endothelin-1 were abolished.…”
mentioning
confidence: 99%